Violence against woman in clinical and hospital settings: Hypotheses of criminal protection (Research, Society and Development, 2025)
The present work aims to address medical violence against women in clinical and hospital contexts, with a focus on the hypotheses of civil, administrative, and criminal liability provided for in the Brazilian legal system. It is based on the constitutional protection of fundamental rights such as life, physical and moral integrity, sexual dignity, and consent, which are pillars of human dignity and demand effective enforcement by the State and society. The research distinguishes medical violence from medical error, highlighting that the former involves intentional or negligent acts that violate patients’ fundamental rights, causing physical, psychological, or moral harm. Although it can affect all genders, the study focuses on violence against women, exposing structural inequalities and practices such as obstetric violence and abuses in gynecological care. The methodology relies on bibliographic analysis of scientific articles, case law, legislation, and official documents related to physicians’ duties and responsibilities. Subcategories of violence with specific legal provisions were identified, stressing the importance of recognition for effective legal responses. Civil liability of health professionals in such cases is a sensitive and complex issue. The lack of specific legislation to punish medical violence remains a significant barrier to accountability. Therefore, articulation between civil, administrative, and criminal spheres is essential to prevent new occurrences, provide effective redress to victims, and strengthen the ethical and legal commitment of professionals.